Prehospital hypoxemia, measured by pulse oximetry, predicts hospital outcomes during the New York City COVID‐19 pandemic - Elizabeth A. Lancet; Dario Gonzalez; Nikolaos A. Alexandrou; Benjamin Zabar; Pamela H. Lai; Charles B. Hall; James Braun; Rachel Zeig‐Owens; Douglas Isaacs; David Ben‐Eli; Nathan Reisman; Bradley Kaufman; et al. (Journal of the American College of Emergency Physicians Open)
Abstract Objective To determine if oxygen saturation (out‐of‐hospital SpO2), measured by New York City (NYC) 9‐1‐1 Emergency Medical Services (EMS), was an independent predictor of coronavirus disease 2019 (COVID‐19) in‐hospital mortality and length of stay, after controlling for the competing risk of death. If so, out‐of‐hospital SpO2 could be useful for initial triage. Methods A population‐based longitudinal study of adult patients transported by EMS to emergency departments (ED) between March 5 and April 30, 2020 (the NYC COVID‐19 peak period). Inclusion required EMS prehospital SpO2 measurement while breathing room air, transport to emergency department, and a positive severe acute respiratory syndrome coronavirus 2 (SARS‐CoV‐2) reverse transcription polymerase chain reaction test. Multivariable logistic regression modeled mortality as a function of prehospital SpO2, controlling for covariates (age, sex, race/ethnicity, and comorbidities). A competing risk model also was performed to estimate the absolute risks of out‐of‐hospital SpO2 on the cumulative incidence of being discharged from the hospital alive. Results In 1673 patients, out‐of‐hospital SpO2 and age were independent predictors of in‐hospital mortality and length of stay, after controlling for the competing risk of death. Among patients ≥66 years old, the probability of death was 26% with an out‐of‐hospital SpO2 >90% versus 54% with an out‐of‐hospital SpO2 ≤90%. Among patients <66 years old, the probability of death was 11.5% with an out‐of‐hospital SpO2 >90% versus 31% with an out‐of‐hospital SpO2 ≤ 90%. An out‐of‐hospital SpO2 level ≤90% was associated with over 50% decreased likelihood of being discharged alive, regardless of age. Conclusions Out‐of‐hospital SpO2 and age predicted in‐hospital mortality and length of stay: An out‐of‐hospital SpO2 ≤90% strongly supports a triage decision for immediate hospital admission. For out‐of‐hospital SpO2 >90%, the decision to admit depends on multiple factors, including age, resource availability (outpatient vs inpatient), and the potential impact of new treatments.